CRITICAL THINKING SKILLS AMONG MEMBERS OF THE IRAQI KURDISTAN PARLIAMENT - Karim , Buhar; Aziz , Omar (Humanities Journal of University of Zakho, 2024)
The research aimed to identify the level of critical thinking skills among members of the Iraqi Kurdistan Parliament, and the significance of the differences in that according to demographic variables: (gender, age, nationality, educational level, years of service in Parliament). The research relied on the descriptive approach in the study, and the research community consisted of (111) male and female members in the fifth session of Parliament. The research sample, which was chosen intentionally, consisted of (95) members (67 males and 28 females), and the researchers used a shortened form of the critical thinking test prepared by Watson-Gleser. The data were processed statistically using the mean, standard deviation, t-test for one sample and two independent samples, one-way analysis of variance, and Cronbach's alpha equation. The results showed that the level of critical thinking skills among members of the Iraqi Kurdistan Parliament, in general, is low, and it was found that there are no statistically significant differences in critical thinking skills due to the variables of gender, age, nationality, level of education, and years of service in Parliament. In light of the results of the research, several recommendations and proposals were presented.